Study of clinical and etiological profile of hypertension in young patients - Sheetal Rudra Naik; Mamatha Tittamegalapalya Ramalingaiah; Aishwarya Ram (Asian Journal of Medical Sciences)
Background: Hypertension significantly impacts global health, leading to coronary heart disease, stroke, and renal disease. Addressing it in young adults is crucial due to its potentially reversible causes and early intervention.